Pandangan Ekonomi Syariah terhadap Praktik Gesek Tunai Pay Later pada GoPay Later - Wulandari, Silvia Anggraeny Sri; Kalimah, Siti (Universitas Islam Negeri Alauddin Makassar, 2024)
Technological advances have made it easier to make transactions, one of which is through paylater payment systems, such as GoPay Later. However, this convenience provides a gap for abuse, especially through the disbursement of paylater limits that are not in accordance with company regulations, known as cash swipe. In this practice, the Gopay Later limit owner uses the services of a third party to disburse the limit through fictitious transactions. This research reviews the concept of an ijarah contract, which means that transactions must not be tied to certain conditions and must be based on the benefits obtained. This research aims to provide further understanding to readers about the importance of conducting transactions according to sharia principles. This research uses descriptive qualitative method with primary data obtained through interviews with service owners. The results show that ijarah contracts in the practice of cash swipe services are allowed if both parties agree and understand the agreement. However, this cash swipe transaction has risks that need to be considered by both parties.